The school chalenge of teaching per subject and the need for knowledge rebinding - Celso José Martinazzo; Óberson Isac Dresch (Universidade Federal de Santa Maria, 2014)
In this paper we propose a reflection on the challenge of school to work the question of knowledge in the form of a subject and the need of rebinding the knowledge. Among the many tasks that historically have always been tasks of school education, there is the commitment to transmission and production of knowledge. When referring to the school as a privileged agency dealing with the issue of knowledge, many implications arising from this statement are faced. It is sought to interpret these implications and possibilities in the light of the contributions of the principles of complexity theory due to the understanding that this paradigmatic matrix one of the privileged references for understanding the process of production of relevant knowledge, i.e., a knowledge that, while it distinguish itself, seeks to promote the rebinding of knowledge.